2024
DOI: 10.3390/coatings14010099
|View full text |Cite
|
Sign up to set email alerts
|

Coatings and Surface Modification of Alloys for Tribo-Corrosion Applications

Robert J. K. Wood,
Ping Lu

Abstract: This review of the tribocorrosion of coatings and surface modifications covers nearly 195 papers and reviews that have been published in the past 15 years, as compared to only 37 works published up to 2007, which were the subject of a previous review published in 2007. It shows that the research into the subject area is vibrant and growing, to cover emerging deposition, surface modification and testing techniques as well as environmental influences and modelling developments. This growth reflects the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 238 publications
(255 reference statements)
0
1
0
Order By: Relevance
“…To overcome this challenge and improve the versatility of polymeric materials in applications that require adhesive bonding, various surface modification techniques are commonly employed. Numerous studies have shown that plasma treatments are some of the most promising surface modification methods [ 9 , 10 ]. These techniques are capable of altering the physical and chemical properties of a material surface, thereby significantly enhancing the surface wettability and adhesion properties without influencing the bulk properties of the material [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this challenge and improve the versatility of polymeric materials in applications that require adhesive bonding, various surface modification techniques are commonly employed. Numerous studies have shown that plasma treatments are some of the most promising surface modification methods [ 9 , 10 ]. These techniques are capable of altering the physical and chemical properties of a material surface, thereby significantly enhancing the surface wettability and adhesion properties without influencing the bulk properties of the material [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, providing the surface of any substrate with specific functionalities (even more than one at the same time) makes the material suitable for applications that would have never been envisaged without that particular surface treatment. Additionally, these newly conferred characteristics do not modify the overall bulk properties of the treated substrate, hence (i) avoiding the use of high amounts of additives/modifiers/fillers that are usually diluted in the material's bulk (thus providing a limited effect), (ii) determining a negligible impact on those properties that do not require any modification, and, finally, (iii) focusing on the most critical area, i.e., the material's surface [1][2][3].…”
Section: Introductionmentioning
confidence: 99%